PENGARUH MOTIVASI BELAJAR DAN MINAT BELAJAR TERHADAP KEMAMPUAN MENULIS KARYA ILMIAH SISWA - Aji Permana; Nurhidayat Nurhidayat (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
The purpose of this study was to determine the effect of motivation and interest in learning on the ability to write scientific papers. The effect of learning motivation and interest in learning shape the ability to write scientific papers. The research method used is a survey method. The sample is randomly selected, 65 students. Data collection was carried out by direct observation techniques and by distributing questionnaires. Data analysis used statistics, namely correlation test, coefficient of determination, and regression test. The results of the multiple linear regression test obtained the following equation: Y = 80,623 + 0,065 X1 + 0,086 X2. The influence of the learning motivation variable (X1) is 44,5%, and the influence of the learning interest variable (X2) is 26,9%. These calculations show that the influence of learning motivation is greater than interest in learning. Then, from the calculation of determination, R square or coefficient of determination of 0,020 means that 20% of the ability to write scientific papers is influenced by learning motivation and interest in learning meanwhile other variables outside the equation influence the rest.